The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1002/celc.201700991
|View full text |Cite
|
Sign up to set email alerts
|

Significant Enhancement of the Photoelectrochemical Activity of CuWO4 by using a Cobalt Phosphate Nanoscale Thin Film

Abstract: Nanostructured CuWO4 photoanodes were fabricated through a facile electrodeposition method, which was followed by annealing the sample at 500 °C for 2 h. The morphologies, crystalline structure, electronic states, optical behaviors, and photoelectrochemical characteristics of the CuWO4 nanomaterial were examined by scanning electron microscopy, X‐ray diffraction, X‐ray photoelectron spectroscopy, UV/Vis spectroscopy, and impedance spectroscopy, showing that the formed triclinic CuWO4 nanoparticles had an indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…70% increase over that of CuWO 4 (0.32 mA•cm −2 ). However, no obvious shift of the OER onset potential is observed, which is also found in other reports on cocatalyst-modified CuWO 4 [26,[39][40][41]. This indicates that the charge-transfer resistance around the onset potential range is quite large and thus even an OER cocatalyst fails to effectively accelerate the charge transfer.…”
Section: Photoactivity and Photostability Of Cuwo4 And Cuwo4/irco-pi ...supporting
confidence: 77%
See 1 more Smart Citation
“…70% increase over that of CuWO 4 (0.32 mA•cm −2 ). However, no obvious shift of the OER onset potential is observed, which is also found in other reports on cocatalyst-modified CuWO 4 [26,[39][40][41]. This indicates that the charge-transfer resistance around the onset potential range is quite large and thus even an OER cocatalyst fails to effectively accelerate the charge transfer.…”
Section: Photoactivity and Photostability Of Cuwo4 And Cuwo4/irco-pi ...supporting
confidence: 77%
“…Note that, in Ref. [40,41], although the authors named the photoanode CuWO 4 , it actually was, as the authors mentioned in the articles, a mixture of WO 3 and CuWO 4 based on the XRD data where unique WO 3 peaks at ca. 33.2 • can be clearly seen.…”
Section: Photoactivity and Photostability Of Cuwo4 And Cuwo4/irco-pi ...mentioning
confidence: 99%
“…Therefore, approaches such as the introduction of effective OER electrocatalyst to minimize the energy penalty associated with water oxidation improved the catalytic efficiency and lowered the excessive potential closely related to the interfacial charge transfer. Specifically, nonprecious and abundant electrocatalysts including Mn-phosphate (MnPO), Co-phosphate, and Ni-based electrocatalysts, have been widely used to reveal the remarkable increase in electrocatalytic properties [10]. Bartlett's group reported that the MnPO-based CuWO 4 photoelectrode exhibited improved PEC performance, corresponding to the cathodic shift of the onset potential for water oxidation by ~ 100 mV and a mild increase in photocurrent density, particularly at low applied bias [11].…”
Section: Introductionmentioning
confidence: 99%
“…Enlighten by the above DFT calculation, we assumed that fabrication of ultrathin CuWO 4 film with high crystallization will be favorable for improving the PEC performance. At present, there are many methods to prepare CuWO 4 thin films, such as reactive co-sputtering, [31] electrodeposition" [32,33] and hydrothermal synthesis. [24,34] However, these methods are usually complicated and the thickness of the film can not be well controlled.…”
Section: Resultsmentioning
confidence: 99%